Jane Smith: 12 Months to Live - Book 1 - Patterson, James ([United States] : Hachette Audio, 2023)
Her name is Jane Smith. To friends and foes, shes Jane Effing Smith. Why? Because shes the best criminal defense attorney in the Hamptons, the elite world of New Yorks rich and infamous. Because shes as good an investigator as she is a lawyer. Because shes tough. Shes strong. A competitive athlete who never settles for second place. As Jane is preparing to defend a high-profile client accused of a triple homicide, shes also hired to revive a cold case, a cluster of unsolved murders. Then another bombshell lands: a devastating medical diagnosis. Terminal. Shes given twelve months to live. But first, she has a trial to win. Unless one of her many enemies kills her first.